N₂ fixation, plant mineral nutrition and C metabolites in cowpea/maize cropping systems - Monakisi, Charlotte (Department of Biological Sciences, 2017)
The objective of this study was (1) quantify N₂ fixation in sole and mixed cropped cowpea, (2) To access nutrient assimilation by component species in the cropping system, and (3) to determine the effects of cropping system on C metabolites. At harvest the dry mass of both cowpea and maize were highest in sole crops. There was a significant difference in % nitrogen of maize and cowpea plants from the different cropping systems. Total nitrogen content was highest in sole cropped maize and cowpea plants with sole cowpea fixing the most N₂. δ¹⁵N values were lower for the shoots of symbiotic cowpea compared to the maize. Root δ¹⁵N values were also generally lower in cowpea than in maize. The %N derived from fixation (Ndfa) was similar for sole, intra and intercropped cowpea. However the amount of N fixed was significantly greater in sole cowpea compared to intra- and intercropped cowpea. When nutrient uptake and assimilation was assessed in the cropping system, it was found that mineral elements such as Ca, Mg, Cu, Zn and B occurred in significantly greater concentrations in the N₂-fixing legume compared to the cereal partner. However the concentration of soluble sugars and starch remained the same for both shoot and roots of cowpea and maize plants in the cropping system.